PENGARUH KONFLIK PERAN, KOMPETENSI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN THE ANVAYA BEACH RESORT & SPA KUTA-BALI - Ariyana, Putu Gede; Novarini, Ni Nyoman Ari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
This research aims to test the return variable conflict influences the role, competence and motivation of work on performance of employees. This research was conducted on The Anvaya Beach Resort & Spa Kuta-Bali using the 77 contracts as employees of the sample slovin using methods specified. Analysis tools on research using SPSS Version 17.0 analysis tool. The results of this study indicate that the variables that conflict the role, competence and motivation of work a positive and significant effect simultaneously against theperformance levels of employees. The role of conflict influential variables negatively to employee performance demonstrated by the significant value of 0.009 smaller than 0.05. While the variable competence and motivation work positive effect on performance of employees demonstrated significant value 0.000 smaller than 0.05.